Peningkatan Minat Belajar Matematika Materi Perkalian Dan Pembagian Metode Dictate (DMP) Siswa Kelas III SDN.Banjarsari 01 Tahun 2014/2015 - Herni, Roh; , Drs. Suwarno, SH., M. Pd (2015)
The background of this problem are: mathematics one of the subjects that make a positif contribution and achieving beneficial intelligent society through critical thingking and logical thingking. The classical problem in mathematics education is low achievement and lack of interest in learning and a desire for learning mathematics in school. The object of this study are: increase interest in learning math multiplication and division material through method dictate (DMP) in the third grade students of SDN. Banjarsari 01 year 2014/2015. The learning method used is method dictate (DMP). Dictate is a way of teaching by providing exercises what has been so that students acquire a certain skill. With the method dictate ( DMP) on mathematics learning multiplication and division material that students are always diligent practice memorize and recite it in the process of multiplication and division. Which will be the application of the method dictate (DMP) 1). Students are more widely through repeated practice, 2) the student is ready use his skills as already accustomed. So that the student's interest in learning mathematics can be well motivated. The result of this study are: increase student interest in learning mathematics multiplication and division matter, namely the method dictate learning process will be more active and motivated achieve the learning goals of students who eventually interest in learning can be achieved. In the learning process of interaction between teacher and students and between students and students. In the interaction of the teacher as a teacher, while students as individual learners.